Persepsi peternak tentang teknologi asap cair (liquid smoke) tempurung kelapa di kelompok ternak satwa mandiri Kabupaten Kediri - Yunita Ninsi Saputri; Wahyu Windari; Nurlaili Nurlaili (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
This study aims to (1) determine the perceptions of farmers about coconut shell liquid smoke technology and (2) determine the factors that influence it. The research method used a descriptive quantitative approach with a survey method. Sampling using saturated samples with some 34 people. Data analysis was performed with descriptive data analysis and multiple linear regression analysis to measure the X factor (age, business experience, business income, cosmopolitan expectations, and interests) to factor Y (Perception). The results of the study showed that farmers with positive/good perceptions of coconut shell liquid smoke technology were 53%, while farmers who had negative perceptions were 47%. The analysis results obtained multiple linear regression equation Y = (4.179) + (-0,119) X1 + (0.208) X2 + (0.114) X3 + (1,475) X4 + (0.297) X5 + (0.490) X6 with R of 0.547 and R2 equal to 0.859. The results of the model summary explain the summary of the model consisting of multiple correlation values (R), 0.927. This shows that there is a high relationship between the variable x (age, business experience, business income, cosmopolitan, hopes, and interests) and the farmers' perceptions of coconut shell liquid smoke technology. The t-test results show the t-count value of the cosmopolitan factor (4.142) and the factor of interest (2.114)> t-table (2.051) at the significance level of α 5%. The factors that influence farmers' perceptions of liquid smoke technology are cosmopolitan and interest. In general, breeders have good perceptions of liquid smoke technology, so that the application of liquid smoke technology in animal husbandry can be applied repeatedly to suppress environmental pollution due to the odor generated by laying chicken manure.